Mechanism of Resistance to S-metolachlor in Palmer amaranth - Gulab Rangani; Matheus Noguera; Reiofeli Salas-Perez; Lariza Benedetti; Nilda Roma-Burgos (Frontiers in Plant Science, 2021)
Herbicides are major tools for effective weed management. The evolution of resistance to herbicides in weedy species, especially contributed by non-target-site-based resistance (NTSR) is a worrisome issue in crop production globally. Glyphosate-resistant Palmer amaranth (Amaranthus palmeri) is one of the extremely difficult weeds in southern US crop production. In this study, we present the level and molecular basis of resistance to the chloroacetamide herbicide, S-metolachlor, in six field-evolved A. palmeri populations that had survivors at the recommended field-dose (1.1 kg ai ha−1). These samples were collected in 2014 and 2015. The level of resistance was determined in dose-response assays. The effective dose for 50% control (ED50) of the susceptible population was 27 g ai ha−1, whereas the ED50 of the resistant populations ranged from 88 to 785 g ai ha−1. Therefore, A. palmeri resistance to S-metolachlor evolved in Arkansas as early as 2014. Metabolic-inhibitor and molecular assays indicated NTSR in these populations, mainly driven by GSTs. To understand the mechanism of resistance, selected candidate genes were analyzed in leaves and roots of survivors (with 1 × S-metolachlor). Expression analysis of the candidate genes showed that the primary site of S-metolachlor detoxification in A. palmeri is in the roots. Two GST genes, ApGSTU19 and ApGSTF8 were constitutively highly expressed in roots of all plants across all resistant populations tested. The expression of both GSTs increased further in survivors after treatment with S-metolachlor. The induction level of ApGSTF2 and ApGSTF2like by S-metolachlor differed among resistant populations. Overall, higher expression of ApGSTU19, ApGSTF8, ApGSTF2, and ApGSTF2like, which would lead to higher GST activity in roots, was strongly associated with the resistant phenotype. Phylogenetic relationship and analysis of substrate binding site of candidate genes suggested functional similarities with known metolachlor-detoxifying GSTs, effecting metabolic resistance to S-metolachlor in A. palmeri. Resistance is achieved by elevated baseline expression of these genes and further induction by S-metolachlor in resistant plants.